Barriers to cervical cancer screening faced by immigrant Muslim women: a systematic scoping review - Yusi Riwayatul Afsah; Noriyo Kaneko (BMC, 2023)
Abstract Background Uptake for cervical cancer screening (CCS) is extremely low among immigrant women, particularly Muslim women, because of barriers related to religious values, beliefs, and fatalism. This scoping review aimed to summarize and analyze the findings of previous studies regarding perceived barriers to CCS among Muslim immigrant women. Methods A search of electronic databases of peer-reviewed articles, including MEDLINE, CINAHL, PubMed, and Scopus was conducted. The following criteria were used for the selection of the articles: (a) the study population consisted of immigrant Muslim women, (b) CCS barriers were the main focus of the study, (c) the articles were original research articles, (d) the research was conducted within the last 10 years, and (d) the study was reported in English language. Results Barriers included sociodemographic factors, economic, language, cognitive, and emotional reactions. The healthcare system was classified as a community barrier, whereas culture and religion were categorized as social barriers. Beliefs that becoming ill and dying is the will of Allah and that health problems are a punishment from God were considered to be major barriers to CCS among immigrant Muslim women. Conclusion Access to health service centers and CCS among Muslim immigrant women is challenging. Information dissemination by health care workers is needed to increase awareness of CCS and access to CCS service points among immigrant Muslim women. Physician recommendations to attend CCS also play an important role.